Peritonitis secondary to spontaneous perforation of a primary gastrointestinal stromal tumour of the small intestine: A case report and a literature review. (2015) - Alessiani, Mario; Gianola, Marco; Rossi, Sabina; Perfetti, Vittorio; Serra, Piero; Zelaschi, Daniela; Magnani, Enzo; Cobianchi, Lorenzo
Highlights: Emergency presentation of a GIST is not uncommon and one of its manifestations is acute abdome. The cases described in the literature are the tip of the iceberg and spontaneous rupture or perforation of GISTs are a far more frequent first presentation of this rare tumour. The jejunum was the more common location of perforation compared to the ileum. Emergency surgery is mandatory and should achieve radical resection. Abstract: Introduction: A few cases of acute abdomen caused by perforation of small-intestinal gastrointestinal stromal tumours (GISTs) have been reported in the literature. Presentation of case: Together with a review of the published cases, here we report a case of an elderly patient with peritonitis due to spontaneous perforation of a GIST of the jejunum. An 82-year-old man was admitted to the emergency unit of our hospital with fever and severe abdominal pain. An abdominal enhanced computed tomography scan detected a 6 cm solid mass in the left upper quadrant adherent to a jejunal loop and surrounded by free fluid and free air. Due to the radiological features of the mass, the diagnosis of a perforation of a GIST arising from the jejunum wall was suspected. The patient underwent emergency laparotomy. Intraoperative findings confirmed diffuse peritonitis secondary to jejunal tumour perforation. A segmental resection of the jejunum containing the mass was performed followed by a mechanical end-to-side anastomosis. The histopathologic examination of the mass confirmed the diagnosis of a perforated GIST of the small intestine (high-risk category). The post-operative course was uneventful and the patient was treated with adjuvant imatinib therapy. Discussion: Twenty-one other cases of spontaneous perforation of small intestine GISTs are reported in the literature and are summarized in the present review. Conclusion: The described case is the tip of the iceberg and spontaneous rupture or perforation of GISTs are a far more frequent first presentation of this rare tumour.